II‐IV Compounds and Related Materials. Issue 7 (July 2016) - Testelin, Christophe; Galtier, Pierre; Sallet, Vincent
Abstract: The 17th International Conference on II–VI Compounds and Related Materials was held at the Campus des Cordeliers, in the historical center of Paris, France, from September 13th to 18th. II–VI 2015 has followed the path of a suc‐cessful series of biennial conferences which started in Durham (UK) in 1983. Recent conferences were or‐ganized in Niagara Falls (USA, 2003), Warsaw (Po‐land, 2005), Jeju (Korea, 2007), Saint Petersburg (Russia, 2009), Mayan (Mexico, 2011), and Na‐gahama (Japan, 2013). The II–VI conference aims at providing an international forum for scientists, students and indus‐try representatives, facilitating the exchange of new ideas and establishing fructuous scientific contacts. The ambition is to report the newest developments in basic and applied research on II–VI and re‐lated compounds such as oxides and chalcopyrite semiconductors. The topics cover also novel synthe‐sis techniques, new physical properties and innova‐tive device development. Let us note that for this last edition, the scope has been extended to Related Mate‐rials like photovoltaic materials and novel 2D sys‐tems (dichalcogenides and topological insulators). Gathering 240 participants, II–VI Paris 2015 has fulfilled its mission, with a scientific pro‐gram presenting three plenary review lectures, 15 in‐vited talks, 64 contributed talks and about 200 con‐tributed poster presentations. A special session has been devoted to the memory of Prof. Fritz Henneber‐ger from Humboldt University, Berlin. Following the conference, this issue of physica status solidi offers a variety of basic and applied studies on optical, electrical and mag‐netic properties of II–VI compounds, related materials and devices. Achievements in practical ap‐plications of II–VI compounds will be found in infrared, visible and UV range detectors, optoelec‐tronic devices, photovoltaics. The proceedings edition also emphasizes new trends and pioneering directions, towards original related materials and devices. A total of 78 articles are published in pss ( b ) (11), pss RRL (1) and pss ( c ) (66). We wish that all participants would appreciate to redis‐cover and thoroughly read some of the nice results presented in Paris. We thank all contributors and reviewers who made the edition of II–VI Paris Proceedings a great success and hope the conference as well as the unique atmosphere of Paris will remain in your heart and memory!